THE PROBLEM OF ANTIBIOTIC RESISTANCE OF HELICOBACTER PYLORI ON THE MODERN STAGE AND ITS CLINICAL SIGNIFICANCE FOR PRACTICAL MEDICINE - A. V. Nalyotov (Медицинский вестник Юга России, 2015)
Th e article off ers an analysis of the literature of recent years dedicated to the development and prevalence of Helicobacter pylori resistance to various antibiotics, which are used for the eradication of this microorganism. Th e reasons of the growth of Helicobacter pylori antibiotic resistance at the present stage have been considered. Th e author describes specifi c issues surrounding diff erent therapeutic options, the ways to overcome this pathogen’s resistance, and the necessary steps in choosing the correct eradication regimens, according to the level of Helicobacter pylori antibiotic resistance. Particular attention is paid to the prevalence of antibiotic resistance of Helicobacter pylori in childhood.